Statistical and numerical investigation of irreversibility for time-dependent Casson-Carreau nanofluid flow driven by curved surface: Regression analysis - P. Kumar; AR. Ajaykumar; F. Almeida; S. Saranya; Qasem Al-Mdallal (Partial Differential Equations in Applied Mathematics, 2025)
Statistical and numerical approach is provided in the current article for Casson-Carreau nanofluid transient flow over continuously elongated sheet of curved feature. The flow is subjected under the various generation, Joule heating, non-linear thermal radiation, activation energy, second order slip, and convective peripheral conditions. Identifying the parameters that optimize the heat transfer rate and using those parameters applying the appropriate statistical tool to optimize the heat transfer rate are the two motives behind this study. A regression analysis is executed on the entropy generated; it has analyzed statistically using response surface methodology. For the issue under consideration, a Runge-Kutta-Fehlberg 4–5th order scheme has been implemented. Here, the study shows that although the Darcy number and first order slip decelerates velocity, the second order slip improves the velocity regime. Additionally, the study has showed that the activation energy parameter leverages the same, while chemical reaction parameter has negative effect on mass dispersion. With an increase in Brinkmann number, entropy production likewise rises, and fluid friction irreversibilities become more prevalent. As unsteadiness and activation energy parameters increase, Sherwood number declines. The visual representation of isotherms and streamlines is presented to display the flow and temperature pattern as a summary of the study. For the experimental setup by RSM, the better correlation coefficient is 99.93 % attained. The Pareto-chart specifies 2.2 to be the vital point for the statistical experimental design considered. For all the levels of heat source parameter and Eckert number, Radiation parameter exhibits positive sensitivity.